ARABIC LANGUAGE DIRECTIVE SPEECH ACT IN SALAHUDDIN AL-AYYUBI MOVIE - Rahmawati, Nailur; Irawati, Retno Purnama; Nawawi, Muchlisin; Sulimah, Sulimah (Arabi : Journal of Arabic Studies, 2020)
A movie can be used as an effective and feasible medium for delivering messages; this served as the study’s rationale. This research acquired communicative speeches in the Salahuddin Al Ayyubi movie. This research aimed to explore two objectives: to describe the form of directive speech acts and to find out the functions of the directive speech acts. The techniques used in this research comprised: (1) uninvolved conversation observation; (2) recording; (3) transcription; and (4) note-taking. The results showed that (1) there were six forms of directive speech acts in the dialogues of "Saladin al-Ayyubi", i.e., imperative, request, invitation, advice, criticism, and prohibition; (2) the functions of directive speech acts in the dialogues of "Saladin al -Ayyubi” are quite varied. The imperative functions had 83 speech data. The request function comprised 52 speech data. The invitation function involved 33 speech data. The advice function consisted of 39 speech data. The criticism act had 13 speech data. The prohibition function consisted of 23 speech data.